NIF Rugby High Foot Campaign from the design side. (May 2016) - Leidinger, J-P; Callahan, D A; Berzak-Hopkins, L F; Ralph, J E; Amendt, P; Hinkel, D E; Michel, P; Moody, J D; Ross, J S; Rygg, J R; Celliers, P; Clouët, J-F; et al.
Abstract: The NIF Rugby High Foot campaign results, with 8 shots to date, are compared with the 2D FCI2 design simulations. A special emphasis is placed on the predictive features and on those areas where some work is still required to achieve the best possible modelling of these MJ-class experiments.